Teaching, learning, and the Holocaust : an integrative approach - Tinberg, Howard (Scholarship of teaching and learning., 2013)
Classroom study of the Holocaust evokes strong emotions in teachers and students. This book assesses challenges and approaches to teaching about the Holocaust through history and literature. The authors apply methods and insights of the Scholarship of Teaching and Learning to examine issues in interdisciplinary teaching, with a focus on the community college setting. They discuss student learning and teacher effectiveness and offer guidance for teaching courses on the Holocaust, with relevance for other contexts involving trauma and atrocity.